1993
DOI: 10.1213/00000539-199302000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Complications After Cardiac Surgery

Abstract: Central nervous system (CNS) complications (disturbance of consciousness, focal motor deficits, and seizures) after coronary artery bypass grafting (CABG) and cardiac valve surgery were studied retrospectively. The incidence of CNS complications was significantly more frequent in CABG (11%, 71/638) than in valve surgery (7%, 24/345). Major contributory factors of CNS complications were preexisting cerebrovascular disease and cardiopulmonary bypass time. In comparison to previous reports, older age, hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Other studies also support this finding, implying that prolonged CPB time is related to an increasing embolic load [3,23] . The pivotal role of surgery time in CABG patients has fully been understood in the literature [23-25] . Brown et al [3] reported that each 60-minute increase in CPB time associates with 30.5% increase in the embolic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also support this finding, implying that prolonged CPB time is related to an increasing embolic load [3,23] . The pivotal role of surgery time in CABG patients has fully been understood in the literature [23-25] . Brown et al [3] reported that each 60-minute increase in CPB time associates with 30.5% increase in the embolic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative neurological dysfunction is a major cause of morbidity after cardiac surgery and occurs in 1%-11% of patients [5][6][7][8][9]. Postoperative neurological dysfunction is a major cause of morbidity after cardiac surgery and occurs in 1%-11% of patients [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent prospective studies, perioperative overt stroke occurs in approximately 1-4% of patients who undergo isolated coronary artery bypass grafting (CABG) (1)(2)(3)(4)(5)(6)(7)(8). Although the incidence of overt sequelae has traditionally been higher in patients undergoing such isolated intracardiac procedures as valve replacement or repair (9)(10)(11)(12)(13), recent studies show that the incidence of stroke for intracardiac procedures now approximates that for isolated CABG (14)(15)(16)(17). In both intracardiac and extracardiac surgery, macroemboli (>200 m in diameter) and microemboli (<40 m in diameter) seem to be responsible for most neurologic complications (1-9, 11, 14, 15, 18).…”
mentioning
confidence: 99%